Peak to average power ratio analysis for OWDM-IDMA system - Awatif Rouijel; Benayad Nsiri; Driss Aboutajdine (2011 International Conference on Multimedia Computing and Systems, 2011)
A major drawback of orthogonal frequency division multiplexing interleave division multiple access (OFDM-IDMA) is the high peak to average power ratio (PAPR) of the transmitted signal. In this paper, the basic principle of Orthogonal Wavelength-Division Multiplexing-Interleave Division Multiple Access (OWDM-IDMA) technique is outlines. The PAPR for multicarrier systems with different pulse shapes is studies, and comparison between OWDM-IDMA and OFDMIDMA techniques in terms of PAPR by estimating the complementary cumulative distribution function (CCDF) of system is provided.
Keywords: PAPR; OWDM-IDMA; OFDM-IDMA; DWPT; IDWPT